2020
DOI: 10.1016/j.jseint.2020.03.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on risk of retear after rotator cuff repair: a systematic review and meta-analysis

Abstract: Hypothesis The purpose of this study was to perform a systematic review and meta-analysis to determine the effect of age on rotator cuff repair failure. The hypothesis of this study was that increased patient age would lead to a higher rate of retears and/or repair failures after rotator cuff repair. Methods We conducted a systematic review and meta-analysis of level I and II studies evaluating patients undergoing rotator cuff repair that also included an imaging assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Our age distribution correlates with similar results of specific studies published by Gauci et al [ 16 ] and Taunton et al [ 21 ]. Age could also play a considerable part in the results since older patients may have a lower functional demand than younger patients or tend to have higher rates of RTC deficiency, which correlates with patient age [ 22 ]. It has been argued that, in comparison to older patients, young patients have higher functional demands and higher expectations of enhanced capacity for social interaction, participation in sports, and exercise [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our age distribution correlates with similar results of specific studies published by Gauci et al [ 16 ] and Taunton et al [ 21 ]. Age could also play a considerable part in the results since older patients may have a lower functional demand than younger patients or tend to have higher rates of RTC deficiency, which correlates with patient age [ 22 ]. It has been argued that, in comparison to older patients, young patients have higher functional demands and higher expectations of enhanced capacity for social interaction, participation in sports, and exercise [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of risk factors reported in meta-analyses of outcomes of rotator cuff surgery that can contribute to a higher rate of re-tearing. These include age [ 55 ], size of the initial tear [ 56 ], level of post-surgical activity [ 57 ], prior corticosteroid administration [ 58 ], low HDL levels [ 59 ] as well as co-existent shoulder pathology or a fibro-inflammatory genotype of the repaired tendon [ 60 ] and further studies will be required to determine the causes of re-tearing following augmentation of RC repairs with BCS.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age has been associated with increased rates of retear following rotator cuff repair. 4,7 Diebold et al described a large single surgeon series of 1600 patients and identified a re-tear rate of 5% in patients under the age of 50 years, 10% re-tear rate in patients aged 50e59 years, 15% in patients aged 60e69 years and 25% in patients aged 70e79 years and increasing to 34% in patients over the age of 80 years. 4 Systemic factors such as low bone mineral density (BMD), hyperlipidaemia (HL) and poor glycaemic control in diabetic patients have also been shown to be significant risk factors associated with failure of rotator cuff repair.…”
Section: Patient Factorsmentioning
confidence: 99%